The Effect Of Capital Structure On Profitability And Stock Returns In Property And Real Estate Companies Listed On The Indonesian Stock Exchange 2015-2020 - Afitrah Reski; Masdupi, Erni (Universitas Negeri Padang, 2024)
This study aims to examine the factors that influence capital structure, profitability and stock returns as well as the relationship between capital structure, profitability and stock returns in property and real estate companies listed on the Indonesia Stock Exchange. Endogenous variables in this study are capital structure, profitability, and stock return, while exogenous variables in this study are firm size, growth, tangibility, liquidity, and volatility. In this study, capital structure and profitability also act as mediating variables. While the sample in this study used purposive sampling method, as many as 44 companies that entered the sample selection criteria. So that 264 total sample analysis units were obtained, but the final sample in this study was 185 sample analysis units due to outlier data. The type of data used in this study is secondary data obtained from the IDX in the form of published financial reports. The method used in this research is path analysis or path analysis using the help of the AMOS 22.0 program. Based on the results of this study, it is found that company size and volatility have no significant effect on capital structure (DAR), while growth, tangibility, and liquidity have a significant effect on capital structure (DAR). Company size, growth, tangibility, liquidity and capital structure have a significant effect on profitability (ROA), while volatility has no significant effect on profitability (ROA). Firm size, growth, tangibility and capital structure (DAR) have no significant influence on stock returns, while liquidity and profitability (ROA) have a significant relationship to stock returns. Capital structure (DAR) is not able to mediate the relationship of firm size and growth to stock returns, while capital structure (DAR) is able to mediate the relationship of tangibility and liquidity to stock returns. Capital structure (DAR) and profitability (ROA) are able to mediate the relationship of growth, tangibility, and liquidity to stock returns, while capital structure (DAR) and profitability (ROA) are not able to mediate the relationship of firm size to stock returns. Profitability (ROA) is able to mediate the relationship between company size, growth, tangibility, and liquidity to stock returns.